2009
DOI: 10.1002/ibd.21012
|View full text |Cite
|
Sign up to set email alerts
|

Role of the C5a receptor (C5aR) in acute and chronic dextran sulfate-induced models of inflammatory bowel disease

Abstract: C5aR exerts detrimental functions in acute colitis, strongly supporting the idea that a C5aR-antagonist might be useful for IBD treatment. However, since the absence of C5aR was no longer protective and in some regards disadvantageous in chronic IBD, future studies should address the efficacy and the possible side effects of a sustained antagonist treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 30 publications
1
43
1
Order By: Relevance
“…The contribution of complement activation to colitis was also confirmed in another experimental model, dextran sulfate sodium (DSS)-induced colitis, showing that milder disease symptoms, less histological damage, and a lower expression of inflammatory mediators were observed in C5aR-deficient C57Bl/6 mice after DSS administration. 43 Although this study further demonstrated a disease-protective role of C5a/C5aR signaling in chronic DSS colitis, our study showed a significant increased production of complement products in affected tissues of UC and CD patients, suggesting that inhibition of complement activation represents a potential regimen for the treatment of IBD. Complement C5a, as terminal products of complement activation, is a potent chemoattractant for many immune cells, including neutrophil, macrophage, and dendritic cells (DC), which recruits them into the sites of inflammation and results in a cascade of release of inflammatory mediators that ultimately leads to tissue damage.…”
Section: F4/80contrasting
confidence: 49%
“…The contribution of complement activation to colitis was also confirmed in another experimental model, dextran sulfate sodium (DSS)-induced colitis, showing that milder disease symptoms, less histological damage, and a lower expression of inflammatory mediators were observed in C5aR-deficient C57Bl/6 mice after DSS administration. 43 Although this study further demonstrated a disease-protective role of C5a/C5aR signaling in chronic DSS colitis, our study showed a significant increased production of complement products in affected tissues of UC and CD patients, suggesting that inhibition of complement activation represents a potential regimen for the treatment of IBD. Complement C5a, as terminal products of complement activation, is a potent chemoattractant for many immune cells, including neutrophil, macrophage, and dendritic cells (DC), which recruits them into the sites of inflammation and results in a cascade of release of inflammatory mediators that ultimately leads to tissue damage.…”
Section: F4/80contrasting
confidence: 49%
“…The complement activation inhibitor K-76 produced symptomatic improvement of UC (20). A strong protective effect of a C5a receptor antagonist has been demonstrated in the TNBS-induced rat colitis model and was confirmed recently in the dextran sulfate sodium (DSS)-colitis mouse model (19,42). Conversely, a study by Deguchi (11) showed that DSS-induced colitis is aggravated in C5a-deficient mice, which suggested that the complement system might play a protective role in the development of this experimental colitis.…”
mentioning
confidence: 74%
“…In this model, colonic mucosal inflammation, ulceration, weight loss, and bloody diarrhea develop upon addition of the drug to drinking water. It is a reliable model that has been widely used to investigate the pathogenesis of IBD (7,13,19,27). Although the exact etiologies remain uncertain, results from research in animal models, human genetics, basic science, and clinical trials have provided important new insights into the pathogenesis of chronic, immune-mediated, intestinal inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The potential importance of complements in the pathophysiology of IBD emerges from the clinical findings of enhanced local secretion of complement components in the intestinal tracts and the increased deposition of terminal complement complexes in the inflamed mucosa of IBD [27][28][29][30]. In addition, observations in experimental models of IBD suggest a critical role for complement activation in the pathogenesis of IBD [29,31].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, observations in experimental models of IBD suggest a critical role for complement activation in the pathogenesis of IBD [29,31]. For example, the development of dextran sulphate sodium (DSS) colitis was aggravated in genetically C5-deficient DBA2/J mice, suggesting a protective role of the complement system in the development of DSS colitis [31].…”
Section: Introductionmentioning
confidence: 99%